Development of a Liquid‐liquid Extraction System for Rhodium(III) by 2‐octylaminopyridine from Weak Malonate Media. Issue 8 (30th June 2016) - Suryavanshi, Vishal J.; Patil, Makrand M.; Kokare, Arjun N.; Zanje, Sunil B.; Pawar, Rupali R.; Anuse, Mansing A.; Mulik, Ganpatrao N.
Abstract: We have developed the extraction method of rhodium(III) from malonate media with 2‐octylaminopyridine (2‐OAP) in xylene at pH 8.0. The quantitative extraction of rhodium(III) with extractant was found by screening of different physicochemical parameters like malonate concentration, extractant concentration, pH, diluents, effect of temperature, aq: org phase ratio, loading capacity of 2‐OAP. The optimum condition was malonate=0.025 M, pH=8.0, 2‐OAP=0.05 M in xylene. The complete stripping of rhodium(III) from the loaded organic phase was carried out with 2 M HCl. Log‐log plot was investigated to determine the stoichiometry of the extracted species and it was found to be 1 : 2 : 1 (metal : acid :extractant). The versatility of the proposed method was checked for extraction and separation of rhodium(III) from binary, ternary mixture of associated metal ions as well as platinum group metals and from the synthetic solution of rhodium minerals and alloys. Abstract : Here we have developed the green solvent extraction method for the separation of rhodium(III) with 2‐octylaminopyridine from binary, ternary mixture of associated metal ions as well as from the platinum group metals. The extraction of rhodium was achieved from the synthetic solution of rhodium minerals and alloys. Quantitative extraction was observed from malonate media at 8.0 pH